Postulat czwartej generacji praw człowieka w politycznym systemie międzynarodowej ochrony – próba filozoficznego uzasadnienia z perspektywy personalizmu etycznego - Mariusz Ciszek (Studia Ecologiae et Bioethicae, 2010)
In my article, I presented conception of the fourth generation worked out by Catholic ethics. Mentioned conception according to Catholic ethics should be the law’s standard in the international system of protection of human rights. I tried to explain a sense of this conception from the philosophy perspective linking to the basic law’s acts.